New transition relationships for the energy characteristics of earthquakes in the Sakhalin region - Safonov, Dmitry A. (Геосистемы переходных зон)
Due to methodological changes in the work of the Sakhalin Branch of the Federal Research Center “Geophysical Survey of the Russian Academy of Sciences” (SB FRC GS RAS), it became necessary to clarify the transition relationships between the energy characteristics of earthquakes in the Sakhalin region used for the magnitude unification of the catalog. To obtain the transition relationships, a sample for the period from 2017 to October 2024 was used from the database of the “Yuzhno-Sakhalinsk” regional information processing center, which is a part of the SB FRC GS RAS. Using the generalized orthogonal regression method, the relationships linking the magnitude of crustal (h less then 40 km ) earthquakes ML and the energy classes KР and KC were calculated, as well as the magnitudes ML and MPVA separately for crustal and deep-focus (h = 250–600 km) earthquakes in the region. The relationship between ML and the magnitude of the Japan Meteorological Agency Mj was also obtained. It was revealed that for shallow Sakhalin earthquakes Mj ≈ ML; for deep-focus earthquakes, an underestimation of the magnitude ML relative to Mj was noted. As the observational data accumulates, it is assumed that the obtained relationships will be refined.